Impact of SARS-CoV-2 infection on patients with myasthenia gravis: a retrospective study in a Chinese population - Liu, Peng; Li, Mengna; Li, Liqing; Jia, Wenli; Dong, Huimin; Qi, Guoyan (Frontiers in Neurology, 2024)
Background and purposeMyasthenia gravis (MG) is characterized by fluctuating muscle weakness due to immune-mediated damage to acetylcholine receptors. Viral infections can exacerbate symptoms of muscle weakness, and the clinical status of patients with MG may influence the outcomes of such infections. Here, we identified factors of symptom exacerbation, severe SARS-CoV-2 infection, and pneumonia in patients with MG who are infected with SARS-CoV-2.MethodsThe clinical characteristics and outcomes of 341 MG patients infected with SARS-CoV-2 across multiple regions in China were determined.ResultsThe median age of the patients was 49 years (range: 35–60 years) and the median disease duration was 4 years (range: 2–8 years). Among the patients, 67 (49.0%) were male and 174 (51.0%) were female. Multivariate analysis indicated that thymectomy [OR, 1.654 (95% CI, 1.036–2.643); p = 0.035], severe SARS-CoV-2 infection [OR, 4.275 (95% CI, 2.206–8.286); p < 0.001], and pyridostigmine bromide [OR, 1.955 (95% CI, 1.192–3.206); p = 0.008] were associated with exacerbation of MG symptoms in patients infected with SARS-CoV-2. Age was significantly associated with severe SARS-CoV-2 infection [OR, 1.023 (95% CI, 1.001–1.046); p = 0.008], while patients with cardiac/vascular comorbidities exhibited an increased likelihood of severe SARS-CoV-2 infection [OR, 3.276 (95% CI, 1.027–10.449); p = 0.045]. Likewise, steroid treatment [OR, 6.140 (95% CI, 2.335–16.140); p < 0.001] was associated with a significantly increased likelihood of severe SARS-CoV-2 infection compared with symptomatic treatment. Additionally, gender [OR, 0.323 (95% CI, 0.120–0.868); p = 0.025] and SARS-CoV-2 severity [OR, 6.067 (95% CI, 1.953–18.850); p = 0.002] were associated with the occurrence of pneumonia.ConclusionWe identified factors that were associated with the exacerbation of MG symptoms in patients infected with SARS-CoV-2, including thymectomy, severe SARS-CoV-2 infection, and the use of pyridostigmine bromide. Due to the retrospective nature of the study, these findings should be interpreted as associations rather than predictive factors. However, the results confirm the established relationships between severe SARS-CoV-2 infection and age, cardiovascular comorbidities, and the use of steroid treatment, suggesting that these factors should be considered when managing MG patients during SARS-CoV-2 infection.